Dilated jugular venous arch mimicking a medial neck mass - A case report - Tran Van Buu; Grégoire Braux; Benoît Pacquelet; Emmanuel Babin; Justin Dugué (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2021)
The Anterior Jugular Venous System (AJVS) comprises a pair of anterior jugular veins and jugular venous arch, which plays an important role in the interconnection between superficial and deep veins. Anatomical variation of the AJVS predisposes one to dangerous complications during procedures involving head and neck region. Furthermore, these aberrant anatomies may manifest in various clinical forms which may be a challenge to diagnose. In the present study, we report a case of a enlarged jugular venous arch inducing a tumor-mimicking lesion in suprasternal notch. The knowledge about these anatomical variations can assist the physicians in interpreting neck masses and preventing iatrogenic injury.